Mass Distributions and Neutron-Proton Ratios of Fragments in Peripheral Heavy-Ion Collisions - Hamide Avcı (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2022)
The mass and average neutron-proton ratio (N/Z) distributions of fragments from multifragmentation of excited projectile nuclei formed in heavy-ion collisions were reproduced theoretically. The experimental measurements in peripheral heavy-ion collisions of 124Sn + 124Sn and 112Sn + 112Sn at 1 GeV/nucleon were carried out with the Fragment Separator (FRS) of GSI. The mass distribution and N/Z ratios of the produced nuclear fragments are calculated in the frame of a statistical approach. Comparisons with the experimental data show that the statistical models are successfully reproduce the mass yields and N/Z measured in the both reaction systems. The calculations in the present paper were carried out for the first time and were not published anywhere else.